Evaluation Study of Design Management in Urban Public Space after Renewal - A Case Study of Chongqing Zhujiang Road - Yuan, Yuan; Khantong, Jiraporn (Nimitmai Review Journal, 2025)
This thesis takes the public space of Chongqin2g urban commercial neighborhood as the research object, and chooses Zhujiang Road as a representative case of public space in renewal. Taking the residents' feeling of use as the most basic judgement standard, we adopt the satisfaction evaluation method of Post-Occupancy Evaluation (POE), combining the knowledge of design management, statistics, architecture, sociology and other disciplines to carry out a post-occupancy evaluation study on the research object. Analyse the humanities, behaviours and feelings of use in the renovated space, and dissect the residents' real thoughts and feelings of use in the renovated space. A hierarchical comprehensive evaluation framework for the renewal of commercial neighbourhoods is built, and the indicator system and methods for the urban public space after renewal are constructed, on the basis of which the planning path for the renewal of urban public space is proposed. Through the post-use evaluation study of the Pearl River Road neighbourhood, it can be seen that the users' satisfaction rating of the overall effect of the renovation of Pearl River Road is 2.756 points (total 5 points), which is in a general state. "Overall spatial layout", "green landscape", "humanistic atmosphere", "employment and income improvement effect The ratings of "overall spatial layout", "green landscape", "humanistic atmosphere", and "employment and income improvement effect" are relatively high, and the regeneration is worthy of recognition in these aspects. However, the ratings for "traffic improvement effect", "pavement signals and markings", and "openness and maintenance" are low, and further renovation is needed.